17-channels S band multiwavelength Brillouin/Erbium Fiber Laser co-pump with Raman source - Ahmad, Harith; Zulkifli, Mohd Zamani; Latif, Amirah Abdul; Thambiratnam, Kavintheran; Harun, Sulaiman Wadi (IOP Publishing, 2009)
In this paper, we propose and demonstrate a stable Brillouin-Erbium Fibre Laser (BEFL) capable of generating up to 17 lasing wavelengths in the Short-Wave length (S-band) region. The proposed setup uses a 7.7 km Dispersion Compensating Fibre (DCF) to act as a non-linear gain medium and a 30 m long Depressed-Cladding Erbium Doped Fibre (DC-EDF) as an optical amplifier for amplification in the S-band region. The proposed BEFL has an optimum tuning range of 1499 to 1502 nm and is capable of generating 17 lasing wavelengths with peak powers of between -20 to -15 dBm when injected with a Brillouin Pump (BP) of 5 dBm at 1499 nm and a Raman Pump (RP) of 300 mW at 1420 nm.